2010
DOI: 10.4168/aair.2010.2.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Beef-Induced Anaphylaxis Confirmed by the Basophil Activation Test

Abstract: Beef allergies are relatively rare, especially in adults. However, clinical manifestations can vary from urticaria, angioedema, anaphylaxis to gastrointestinal symptoms. Currently available tests, such as skin testing or in vitro determination of beef-specific immunoglobulin E (IgE), do not provide an accurate diagnosis of beef allergy. The recent development of the basophil activation test (BAT) presents a new opportunity for the diagnosis of food allergies. Here, we report a 37-year-old woman with a history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…For the functional in vitro test for allergic reactions to cefaclor, a basophil activation test (BAT) was performed using flow cytometry (FACScantoII; BD Immunocytometry Systems, San Jose, CA, USA), using CD63 antibody according to previously described methods. 13 Patients' basophils were incubated with cefaclor at dilutions of 1.6×10 -3 , 1.6×10 -2 , and 1.6×10 -1 mg/mL for 30 minutes. BATs were conducted for two healthy controls under the same condition to exclude a nonspecific activation of basophil.…”
Section: Methodsmentioning
confidence: 99%
“…For the functional in vitro test for allergic reactions to cefaclor, a basophil activation test (BAT) was performed using flow cytometry (FACScantoII; BD Immunocytometry Systems, San Jose, CA, USA), using CD63 antibody according to previously described methods. 13 Patients' basophils were incubated with cefaclor at dilutions of 1.6×10 -3 , 1.6×10 -2 , and 1.6×10 -1 mg/mL for 30 minutes. BATs were conducted for two healthy controls under the same condition to exclude a nonspecific activation of basophil.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale of this test is the change in the phenotype of activated basophils after in vitro incubation of the patient’s whole blood with the allergen. The BAT is a useful complementary tool to the in vitro diagnosis of FA caused by milk, egg, peanut and wheat [ 69 , 70 ] when IgE may be involved. Interestingly, a recent study of 20 peanut-allergic children showed that when basophils were stimulated with decreasing doses of allergens until threshold sensitivity was reached, 19 were negative to peanut but 17 were positive to rAra h 8, suggesting that the children sensitized to Ara h 8 but not peanut storage proteins may be at risk of systemic allergic reactions, especially when eating large amounts of peanuts [ 70 ].…”
Section: Diagnostic Methods For Food Allergymentioning
confidence: 99%
“…The sensitivity of BAT to different drugs ranges between 36% and 97.7%, with a specificity of approximately 93% [150] . There was a case that the SPT and serum sIgE to beef, pork and milk allergens showed negative results, but the BAT showed significant positive results [152] . The positive SACTs will confirm the diagnosis of allergy, and the substances that the patients are allergic to.…”
Section: Allergen-specific Immunoglobulin Testsmentioning
confidence: 99%